Bigger profits for sun-dried cocoa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
A new technique is helping cocoa farmers in Uganda earn better prices for their crop up to 25% more in some cases...